PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT BERBASIS MEDIA QUESTION CARD TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA DI SD - Amanda Deliya Putri; Mustamiroh; Iksam; Tri Wahyuningsih (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This research is motivated by the low learning outcomes of fourth-grade students of SD Negeri 007 Samarinda Ulu, especially in the subject of Pancasila Education. This is caused by the use of models in learning activities that are not yet oriented so that students can be more active in the learning process. The aim of this study is to determine the effect of the Cooperative Learning Model of the Teams Games Tournament (TGT) Type Based on Question Card Media on the Learning Outcomes of Pancasila Education on Mutual Cooperation Material for Class IV of SDN 007 Samarinda Ulu in the 2023/2024 Academic Year. The type of experimental research used is Quasi Experimental with a research design of Nonequivalent Control Group Design. The population used in this study were all students of grades IV A and IV C of SD Negeri 007 Samarinda Ulu. In this study, there was a control class that used a direct learning model and an experimental class with a total sample of 50 people. Data collection techniques used in this study consisted of tests and documentation. Thus, the research instruments consisted of pretest and posttest sheets, as well as documentation guidelines. Meanwhile, the data analysis techniques used in this study are normality test, homogeneity test, and hypothesis test using Mann-Whitney test because the research results obtained are not normally distributed and homogeneous. The results of the research from hypothesis testing using Mann-Whitney test, show that the Asymp.Sig. (2-tailed) value of the experimental class and the control class with a sample size of 50 is 0.000. Based on the basis of the Mann-Whitney test decision making, if the Asymp.Sig. (2-tailed) value ≤ 0.05 then ha is accepted and Ho is rejected. Thus, because the Asymp.Sig. (2-tailed) value obtained is smaller than 0.05, it can be concluded that there is an influence of the Cooperative Learning Model of Teams Games Tournament (TGT) Type Based on Question Card Media on the Learning Outcomes of Pancasila Education on Mutual Cooperation Material for Class IV SDN 007 Samarinda Ulu in the 2023/2024 Academic Year.